Local Th1/Th2 Cytokine Expression in Experimental Murine Vaginal Candidiasis - 欧阳为相 陈善娟 刘志香 吴艳 李家文 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
In order to investigate the expression of Th1 and Th2 cytokines in the vaginal candidiasis caused by Candida, the fungal vaginitis model was established in female ICR mice by intravaginal inoculation of suspension of C. albicans after the animals were pretreated with estradiol. Reverse transcriptase-polymerase chain reaction （RT-PCR） was used to detect the expression of IL-2, IL-4, IL-10 and TGF-β1 in the vagina in the mice of different groups at different time points after the beginning of the experiment. The average expression level of IL-2 mRNA in group D （estrogen-treated mice） was significantly higher than that in groups H （estrogen-untreated mice） and I （control group） on the day 2. The average expression level of IL-4 mRNA in group D was significantly higher than that in groups I and H on the day 5. The average expression level of IL-10 mRNA in group D was significantly higher than that in groups H and I from day 7 to 11. The average expression level of TGF-β1 mRNA in group D was significantly higher than that in groups H and I at all time points. It was concludes that the high-level expression of IL-2 mRNA during early infection was associated with clearance of mucosal C. albicans, and the high-level expression of IL-10 mRNA during late stage of the infection was related to susceptibility to infection. TGF-β1 may play a predominant role when the virtual absence of changes in other Th-type cytokines during infection.